Malorie's Maternal Instinct in Josh Malerman's Bird Box - Syahputra, Hadi Firmanto; Rahayu, Anik Cahyaning (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This study is entitled Malorie’s Maternal Instinct in Josh Malerman’s Bird Box. This study analyzes how Malorie’s maternal instinct shown in Josh Malerman’s Bird Box. The objective of the study is to find out the kinds and the impacts on her children in the novel. The data are taken from the novel Bird Box by Josh Malerman, Bird Box as the data source. Qualitative method is used to analyze the novel. Because maternal instinct relates to psychological problem, this study uses psychological approach. The psychological theory used is Teresa Heffernan’s Motherhood as the theory. The result of this research shows that Malorie has five maternal instinct. These aspects are nurturing, protective, sacrifice, resilience and strength, as well as complexity and imperfection. The impacts also shown are strength, discipline, and survival skills. Malorie’s maternal instinct is based on her connection with her children, Boy and Girl. However, Malorie’s journey shows that a maternal instinct while imperfect, scary, and sometimes mean is a strong and unbreakable force of love and strength. Malorie is finally able to demonstrate which shows that being her maternal instinct can also help them and her children get through difficult times.